2018
DOI: 10.1007/s12223-018-0637-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of clarithromycin heteroresistance among Helicobacter pylori strains isolated from the antrum and corpus of the stomach

Abstract: Mixed infections and heteroresistance of Helicobacter pylori contribute to decreased efficacy of treatments. This study aimed to investigate frequency of clarithromycin heteroresistance and its link with mixed infections, medication history, and disease severity. A total of 40 pairs of H. pylori strains were isolated from the antrum and corpus of 97 patients. Susceptibility of the strains to clarithromycin was measured by agar dilution method. Site-specific mutations of 23S rRNA at A2143G, A2142G, and A2142C p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…From the 131 articles, 65 were excluded for the following reasons: meta‐analysis, review, non‐original research, conference abstract and article without full text (n = 55), and non‐relevant data or no data for susceptibility testing or no resistance data (n = 10). Finally, 66 studies 4,16‐80 were included in this systematic review and meta‐analysis (Supplementary Table ).…”
Section: Resultsmentioning
confidence: 99%
“…From the 131 articles, 65 were excluded for the following reasons: meta‐analysis, review, non‐original research, conference abstract and article without full text (n = 55), and non‐relevant data or no data for susceptibility testing or no resistance data (n = 10). Finally, 66 studies 4,16‐80 were included in this systematic review and meta‐analysis (Supplementary Table ).…”
Section: Resultsmentioning
confidence: 99%
“…[35][36][37] These genetic traits might promote the coexistence of several strains with different antibiotic Typing CLA AMX LVX TET MET G9 R S S S S G9-1 1 ABD R S S S S G9-2 ABD R S S S S G9-3 ABD R S S S susceptibilities or different genotypes colonizing a single host, which is defined as H. pylori heterogeneity, and has been reported in several studies. 29,31,38,39 In this study, RAPD-PCR and cagA typing was used for distinguishing the heterogeneity of intra-patient strains of H. pylori. Among several genotyping methods applied to H. pylori, RAPD-PCR is considered to be ideal, because it is a simple, rapid, and low-cost means of distinguishing H. pylori isolates.…”
Section: Discussionmentioning
confidence: 99%
“…18,31,33,34,[41][42][43][44][45][46][47] Bacterial infection resulting in more than one RAPD-PCR banding pattern within an individual patient is considered to indicate mixed infections. 28,31 Farzi et al 39 reported 40 intra-patient H. pylori strains isolated from the antrum and corpus of 97 patients, with isolate diversity in resistance to clarithromycin detected in 17.5% (7/40) of the patients. Additionally, they found that the heteroresistant strains were mostly derived from pre-existing strains in each patient rather than from mixed-type infection.…”
Section: Discussionmentioning
confidence: 99%
“…strains, which may provide incorrect information for clinical treatment. 6 The genotyping method could significantly shorten the time needed to obtain antibiotic susceptibility data for H. pylori. This method has been explored since 1996.…”
Section: Genotype Profiles Of Helicobacter Pylori From Gastric Biopsimentioning
confidence: 99%
“…4,5 In addition, as a standard method to detect antibiotic susceptibility, the E-test method cannot distinguish heteroresistant Genotype profiles of Helicobacter pylori from gastric biopsies and strains with antimicrobial-induced resistance strains, which may provide incorrect information for clinical treatment. 6 The genotyping method could significantly shorten the time needed to obtain antibiotic susceptibility data for H. pylori. This method has been explored since 1996.…”
Section: Introductionmentioning
confidence: 99%